Religious Practices in The Butale Hajj Tradition of The Kerinci Regency Community - Susanti, Susi; Darlius, Darlius (AL-MUTSLA, 2025)
This research is related to the religious rituals carried out by the Sinjau Laut Kerinci community before carrying out the Hajj pilgrimage, who always carry out the traditional bertale. This research method is qualitative, the data is obtained through direct observation and interviews with prospective Hajj pilgrims and community figures related to the Hajj tradition. Then the data found was analyzed using descriptive techniques. The Hajj tale is a means of connecting friendship and brotherhood in the Sitinjau Laut community, but today the Hajj tale which is carried out late at night has a negative impact on prospective Hajj pilgrims and the community. According to Islamic law, the hajj tale tradition is permissible as indicated by the poetry performed by the Prophet's companions when carrying out activities for self-motivation.